Molecular Diversity of Pepper yellow leaf curl Indonesia virus (PepYLCIV) the Cause of Yellow Leaf Curl Disease in Chili Pepper (Capsicum frutescens) in Tuban Regency, East Java, Indonesia - Nurenik, Nurenik; Rastono, Adi (Jurnal Perlindungan Tanaman Indonesia, 2025)
Yellow leaf curl disease caused by Begomovirus is a significant threat to chili peppers in Indonesia. This disease has been widespread at several chili pepper production centers in Java, Sumatra, Bali, Lombok, and Sulawesi. Tuban Regency is one of the chili peppers (Capsicum frutescens L.) production centers in East Java, but research on Begomovirus infection is still limited. The study aimed to molecularly characterize and identify Begomovirus that infect chili pepper plants in Tuban. The research method includes symptom observation in the field in four subdistricts in Tuban, molecular detection via PCR, and sequences analysis. Types of symptoms found in chili pepper plants in Tuban were yellowing, curling, curving, green mosaic, leaf cupping upward and downward, and reduction in leaf size. All samples from Grabagan, Bancar, Soko, and Jatirogo Subdistricts were infected by Begomovirus based on the AV1 gene (coat protein) using PCR techniques with target 580 bp DNA fragments. Sequence homology results proved that the pepper yellow leaf curl Indonesia virus (PepYLCIV) of the genus Begomovirus infected chili pepper plants in Tuban. The phylogenetic tree demonstrated that all isolates from Tuban (PQ187395 - PQ187398) were closely related and within the same group as the PepYLCIV isolates from Ngablak Subdistrict, Magelang Regency, Central Java, Indonesia (OP846605). These isolates from Tuban formed a separate group from PepYLCV Malaysian isolates (MW389931).